Assessment of bacterial positivity rate changes in anesthesia machine internal circuits within recovery rooms and associated risk factors - Shuxiao Zhang; Jingwu Ge; Xuelong Zhou; Yanhong Ji; Junjie Hong; Wensu Xu; Tonglai Li (BMC Anesthesiology)
Abstract Objective The objective of this study is to investigate bacterial proliferation within the internal circuits of anesthesia machines in post-anesthesia care units (PACUs) following the implementation of the new protocol, where ‘a single dedicated external circuit is used for each individual patient.’ This measure was introduced during the COVID-19 pandemic, in alignment with a novel prevention and control strategy. Methods Using the observational technique, we analyzed anesthesia machines in PACUs between July and September 2022. The internal circuits of the anesthesia machines were disinfected every two weeks. Samples were obtained from the internal circuits on the 3rd, 5th, 7th, 10th, 12th, and 14th day following disinfection for bacterial culture. Changes in the positivity rate of bacteria in the internal circuits over time were analyzed using the generalized estimating equation. The anesthesia machines were divided into the positive group (n = 9) and the negative group (n = 41) based on the sampling results on the 14th day after disinfection. Risk factors for positive bacterial culture results in anesthesia machines in PACUs were analyzed using single-factor modified Poisson analysis and multi-factor modified Poisson regression analysis. Results The positivity rates of the internal circuits of anesthesia machines in PACUs on the 3rd, 5th, 7th, 10th, 12th, and 14th day following disinfection were 10%, 14%, 12%, 20%, 16%, and 18% respectively. There were no statistically significant differences when the positive rates of the next five time points and the third day were compared (P > 0.05). Risk factors for the contamination in the internal circuits of anesthesia machines was the number of elderly patients and the overall surgical use duration, with the difference was statistically significant (P < 0.025). Conclusion Amid the COVID-19 pandemic, characterized by the adoption of new prevention and control protocols, the disinfection interval for internal circuits of anesthesia machines in PACUs may potentially be extended. However, the emphasis of disinfection should still be placed on those anesthesia machines that have been used for a longer cumulative surgical duration and by a higher number of elderly patients over 60 years old. This approach ensures that resources are allocated effectively.